Cdk1 Inhibition Induces Mutually Inhibitory Apoptosis and Reactivation of Kaposi's Sarcoma-Associated Herpesvirus - Li, Xudong (American Society for Microbiology, 2012)
Primary effusion lymphoma (PEL) cells are predominantly infected by the latent form of Kaposi's sarcoma-associated herpesvirus (KSHV), with virus reactivation occurring in a small percentage of cells. Latency enables KSHV to persist in the host cell and promotes tumorigenesis through viral gene expression, thus presenting a major barrier to the elimination of KSHV and the treatment of PEL. Therefore, it is important to identify cellular genes that are essential for PEL cell survival or the maintenance of KSHV latency. Here we report that cyclin-dependent kinase 1 (Cdk1) inhibition can induce both apoptosis and KSHV reactivation in a population of PEL cells. Caspases, but not p53, are required for PEL cell apoptosis induced by Cdk1 inhibition. p38 kinase is activated by Cdk1 inhibition and mediates KSHV reactivation. Interestingly, upon Cdk1 inhibition, KSHV is reactivated predominantly in the nonapoptotic subpopulation of PEL cells. We provide evidence that this is due to mutual inhibition between apoptosis and KSHV reactivation. In addition, we found that KSHV reactivation activates protein kinase B (AKT/PKB), which promotes cell survival and facilitates KSHV reactivation. Our study thus establishes a key role for Cdk1 in PEL cell survival and the maintenance of KSHV latency and reveals a multifaceted relationship between KSHV reactivation and PEL cell apoptosis.